2012
DOI: 10.1371/journal.ppat.1002679
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Herpes Simplex Virus Type 1 (HSV-1) into the Distal Axons of Trigeminal Neurons Favors the Onset of Nonproductive, Silent Infection

Abstract: Following productive, lytic infection in epithelia, herpes simplex virus type 1 (HSV-1) establishes a lifelong latent infection in sensory neurons that is interrupted by episodes of reactivation. In order to better understand what triggers this lytic/latent decision in neurons, we set up an organotypic model based on chicken embryonic trigeminal ganglia explants (TGEs) in a double chamber system. Adding HSV-1 to the ganglion compartment (GC) resulted in a productive infection in the explants. By contrast, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 102 publications
2
98
0
2
Order By: Relevance
“…HSV-1 tegument contains virion protein 16 (VP16, also known as UL48 and a-TIF) (Zhu & Courtney, 1994) and immediate-early proteins ICP0 (Yao & Courtney, 1992) and ICP4 (Bibor-Hardy & Sakr, 1989). Following virus entry into most, if not all cell types, but especially neurons cultured from human or rat dorsal root ganglia, HSV-1 VP16/UL48, an integral part of the virus tegument (Elliott et al, 1995), is shed from the nucleocapsid as it undergoes transaxonal retrograde transit (Antinone & Smith, 2010;Hafezi et al, 2012). Free VP16/UL48 in the axon and cytosol (Aggarwal et al, 2012) associates with host cell factor (HCF)-1 through a conserved tetrapeptide motif found in most basic leucine-zipper proteins (Freiman & Herr, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…HSV-1 tegument contains virion protein 16 (VP16, also known as UL48 and a-TIF) (Zhu & Courtney, 1994) and immediate-early proteins ICP0 (Yao & Courtney, 1992) and ICP4 (Bibor-Hardy & Sakr, 1989). Following virus entry into most, if not all cell types, but especially neurons cultured from human or rat dorsal root ganglia, HSV-1 VP16/UL48, an integral part of the virus tegument (Elliott et al, 1995), is shed from the nucleocapsid as it undergoes transaxonal retrograde transit (Antinone & Smith, 2010;Hafezi et al, 2012). Free VP16/UL48 in the axon and cytosol (Aggarwal et al, 2012) associates with host cell factor (HCF)-1 through a conserved tetrapeptide motif found in most basic leucine-zipper proteins (Freiman & Herr, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is possibly due to loss of specific transcription factors from the tegument of the incoming virion as it makes its way along the axon to the nucleus, thus shifting the balance between viral lytic gene expression and latency (Hafezi et al, 2012;Roizman & Sears, 1987). In our experiments, we did not restrict infection of neurons to a specific substructure of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that infection of neurons at the level of the cell stroma favours an acute infection; in contrast, infecting neurons through their axonal termini favours a latent infection (Hafezi et al, 2012). This effect is possibly due to loss of specific transcription factors from the tegument of the incoming virion as it makes its way along the axon to the nucleus, thus shifting the balance between viral lytic gene expression and latency (Hafezi et al, 2012;Roizman & Sears, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Dès sa pénétration dans le noyau des cellules épithéliales, le génome viral interagit avec des histones, mais sans aboutir à une chromatini- Glycoprotéines transcripts), seul gène viral à s'exprimer pendant la latence [1,2]. Dans les neurones sensitifs, VP16 n'est pas efficacement transportée le long des axones et n'arrive pas aux noyaux [16,17]. De plus, dans les neurones, HCF1 est détectée seulement dans le cytoplasme et elle est incapable d'interagir avec VP16, car inaccessible [18].…”
Section: éTablissement De L'infection Lytiqueunclassified
“…Il en résulte que le complexe VP16/ OCT1/HCF1 ne se forme pas, ce qui se traduit par un déficit de l'expression des gènes très précoces (Figure 2). Une étude récente apporte une contribution majeure concernant le rôle de VP16 dans les étapes très précoces de l'infection latente [17] : des explants de ganglions trijumeaux ont été mis en culture dans un dispositif à deux compartiments, permettant de séparer les corps cellulaires (compartiment central) des terminaisons nerveuses (compartiment périphérique). En introduisant le virus dans l'un ou l'autre de ces compartiments, on constate que l'infection des corps cellulaires conduit à une infection lytique, alors que l'infection des terminaisons nerveuses mène presque toujours à une infection quiescente, caractérisée par une très faible expression des gènes lytiques et une forte transcription des gènes LAT.…”
Section: éTablissement De L'infection Lytiqueunclassified